Pengaruh Kompetensi Dan Tacit Knowledge Terhadap Kinerja Karyawan - Suri, Desy Kartika, Dr. Anton Agus Setyawan, S.E.,M.M (2016)
The purpose of this study was to determine: 1. To analyze the effect of competence on employee performance, 2. To analyze the effect of tacit knowledge on employee performance. Samples of this study was 120 employees of PT. Indo Acidatama Kebakkramat. The sampling technique of this research is simple random sampling. the type of data in this study using primary data from questionnaires. The test instrument used is Test Validity and Test Reliability. Methods of data analysis in this study using multiple analysis, F test and t test showing that:(1) The existence of positive values and competencies and significant effect on the performance of employees indicated the significant value of 0.000 (p> 0.05) (2) There is a positive and significant impact on the performance of the tacit knowledge of employees indicated by the significant value of 0.014 (p <0.05).From this study it can be concluded that employees of PT. Indo Acidatama Kebakkramat requires competence and tacit knowledge to improve employee performance.